Elaboration, caractérisation de charbons actifs fonctionnalisés et étude de leurs propriétés en adsorption de composés organiques. - Naziha, LADJAL (Université de m'sila, 2013)
Activated carbon were prepared by thermochemical activation at 450 °C of the shell of apricot stone for varions ratios of impregnation of phosphoric acid : 30, 60, 90, 120,150 and 180 % by mass. These coals were characterized, for their surface chemistry, by infra-red spectroscopy (FTIR) analysis, selective neutralization « Boehm titration », measurements of the point of zero charge (pHPZC), and for their porous structure, by nitrogen adsorption at 77 K, methylene bleu adsorption and iodine index test. Activated carbons prepared from shell of apricot stone of slightly acid surfaces (pHPZC ~ 6) were compared with a commercial activated carbon (Sigma Aldrich) (SBET ~ 732 m2.g-1) of basic surface (pHPZC ~ 9,4) for their properties of adsorption of the methylene bleu, of iodine and an anionic dye « Red Nylosan N-2RBL ». Alow ratio of impregnation (XP ≤ 30 %) leads to microporous activated carbon with few mesopores and low specific surface area (SBET ~ 880 m2.g-1), while a high ratio (XP > 30%) produces essentially mesoporous active carbon with a specific surface area reaching 1975 m2.g-1 and a porous volume of 1,37 cm3.g-1 for an exclusively mesoporous CAP180, corresponds of the loss of mass activation ~ 67%. The adsorption experiments were carried out according to the pH of medium between 2 and 12, the contact time and the concentration of azo (anionic) dye « Red Nylosan N-2RBL ». A law of seccond order is well adapted to simulate the kinetics of dye adsorption on activated carbon. The adsorpion isotherms of the dye « Red Nylosan N-2RBL » were studied at a temperature 20 °C. The langmuir model, a typical monolager adsorption, which reproduces the best experimental adsorption isotherms. The different adsorption capacities of activated carbons fallow the fallowing order : CAP180 > CAP150 > CAP120 > CAC > CAP90 > CAP60 > CAP30 indicating that the azo (anionic) dye « Red Nylosan N-2RBL » preferably adsorbed in the mesopores which are accessible to this molecule. The adsorption capacity of the activated carbons (CAP30 and CAP60) and CAC is very sensitive to the pH variation and the transition in the mode of adsorption, due to electrostatic interactions observed at pHS corresponding to the changes of ionic species of the molecule of dye (pH = pKai of the dye) and also depending on the polarity of the surface sites of the activated carbon (pH < pHPZC) the surface of activated carbon is positively charged and (pH > pHPZC) the surface of activated carbon is negatively charged.
Keywords: The shell of apricot stone, H3PO4 activated carbons, surface chemistry, porosity, azo (anionic) dye adsorption.